Aconitine induces cardiomyocyte damage by mitigating BNIP3‐dependent mitophagy and the TNFα‐NLRP3 signalling axis. (27th October 2019) - Peng, Fu; Zhang, Nan; Wang, Chunting; Wang, Xiaoyun; Huang, Wei; Peng, Cheng; He, Gu; Han, Bo
Abstract: Objectives: Aconitine, the natural product extracted from Aconitum species, is widely used for the treatment of various diseases, including rheumatism, arthritis, bruises, fractures and pains. However, many studies have reported cardiotoxicity and neurotoxicity caused by aconitine, but the detailed mechanism underlying aconitine's effect on these processes remains unclear. Materials and methods: The effects of aconitine on the inflammation, apoptosis and viability of H9c2 rat cardiomyocytes were evaluated by flow cytometry, Western blot, RNA sequencing and bioinformatics analysis. Results: Aconitine suppressed cardiomyocyte proliferation and induced inflammation and apoptosis in a dose‐ and time‐dependent manner. These inflammatory damages could be reversed by a TNFα inhibitor and BNIP3‐mediated mitophagy. Consistent with the in vitro results, overexpression of BNIP3 in heart tissue partially suppressed the cardiotoxicity of aconitine by inhibiting apoptosis and the NLRP3 inflammasome. Conclusions: Our findings lay a foundation for the application of a TNFα inhibitor and BNIP3 to aconitine‐induced cardiac toxicity prevention and therapy, thereby demonstrating potential for further investigation.